Heart rate differences between right and left unilateral electroconvulsive therapy. Issue 1 (January 1994) - Swartz, C M; Abrams, R; Lane, R D; DuBois, M A; Srinivasaraghavan, J
Abstract : Left and right unilateral electrode placements were alternately applied in electroconvulsive therapy given to 21 men with melancholia. Accompanying heart rate elevations were greater following right unilateral treatment than left unilateral, apparently because of longer persistence of peak rates. This is consistent with right cerebral hemisphere superiority in the control of heart rate activity in neurologically intact humans.